Helminthiasis and Hygiene Conditions of Schools in Ikenne, Ogun State, Nigeria - Ekpo, Uwem Friday; Odoemene, Simon Nnayere; Mafiana, Chiedu Felix; Sam-Wobo, Sammy Olufemi (PLOS Neglected Tropical Diseases, 2008)
Author SummaryWe studied intestinal helminth infection status in primary-school children and the hygiene conditions of primary schools in Ikenne Local Government Area of Ogun State, Nigeria in order to help guide the development of school-based health programmes. Two government-owned schools (one urban and the other rural) plus one privately owned school participated in the study. Demographic data from 257 children showed that the number of schoolchildren gradually decreased as their ages increased in all the three schools. The sex ratio was proportional in the urban school until primary level three, after which the number of female pupils gradually decreased, whereas in the private school, sexes were proportionally distributed even in higher classes. The prevalence of helminth infection in 232 of the children, however, was 54.9%, 63.5%, and 28.4% in the urban government, rural government, and private school, respectively. Ascaris lumbricoides was the most common parasite, followed by Trichuris trichiura, Taenia species, and hookworm in the three schools. Infection in the government-owned schools was significantly higher than in the private school (p<0.0005). The hygiene condition in the three schools indicated that water supply and sanitation were poorer in government schools than in the private school. We therefore propose that school health programmes such as deworming, health education, and improvement of hygiene conditions, be undertaken in government-owned schools.